Thabo Mbeki the dream deferred - Gevisser, Mark. (Johannesburg Jonathan Ball, 2007)
What happens to a dream deferred? This question, from one of Thabo Mbeki's favourite poems by Langston Hughes, provides the thread for this magisterial biography of the second president of a democratic South Africa. In the long shadow of Nelson Mandela, Mbeki attempted to forge an identity for himself as the symbol of modern Africa. Mark Gevisser brings to life the voices and places that made Thabo Mbeki: the frontier of the Eastern Cape; 'Swinging' Britain and neo-Stalinist Moscow in the 1960s; the fraught world of African exile; the confusion of the transition. He examines the meaning of home and exile; of fatherhood and family. He tells the story of South Africa's black elite over a turbulent century - from 'black Englishman' to revolutionaries to heads of state - and Mbeki's own transition from doctrinaire communism to economic liberalism. Thabo Mbeki: The Dream Deferred is a work of deep scholarship and a gripping, highly readable story. By tracing the path of Mbeki's life, it sheds new light on his political personality and provides unprecedented insight into the dramatic role he has played in South African history.
Includes bibliographical references (p. 845-874) and index
Keywords: Mbeki, Thabo